73. Proposal of a quality control protocol for the SYRMA-3D project: Breast CT with synchrotron radiation. (December 2018) - Contillo, A.; Veronese, A.; Brombal, L.; Donato, S.; Rigon, L.; Taibi, A.; Tromba, G.; Longo, R.; Arfelli, F.
Abstract : Purpose: Breast Computed Tomography (CT) is a dedicated 3D imaging modality that provides a complete volumetric reconstruction of the uncompressed organ, thus matching a high image quality with an acceptable delivered dose. The SYRMA-3D collaboration is developing the first clinical trial of phase-contrast breast CT with synchrotron radiation at the Elettra synchrotron facility in Trieste. We present a proposal for a Quality Control (QC) protocol, including a custom made QC phantom that was designed and built by the laboratories of the University of Ferrara. Methods: The synchrotron beam is monochromatic in the energy range 8.5–40 keV. The images were acquired with a photon counting detector placed at about 2 m from the organ, so as to generate a phase contrast signal. The QC phantom consists of a water filled PMMA cylinder, hung from the patient support through the breast aperture. It contains several inserts that allow measurements of geometric alignment, reconstruction uniformity and linearity, low and high contrast resolution. Results: CT images of the phantom were acquired at several beam energies within the range of interest, to explore the energy dependence of the results. Uniformity and linearity appeared to be preserved by the reconstruction for all energies. Conversely, low contrast details exhibited a more pronounced dependence on the energy choice. Finally, the visibility of high contrast details was always found above acceptance levels. Conclusions: The main goal of the study was to verify the compatibility of the QC phantom with the experimental environment of the SYRMA-3D project, and to test the validity and feasibility of the proposed QC protocol. With minimal modifications, they proved viable instruments to perform the necessary quality assessments for the innovative diagnostic device developed by the SYRMA-3D collaboration.